Armstrong's handbook of human resource management practice : a guide to the theory and practice of people management - Armstrong, Michael, 1928- (Kogan Page, 2026)
Armstrong's Handbook of Human Resource Management Practice by Michael Armstrong and Stephen Taylor is a leading HRM textbook for undergraduate and postgraduate students, as well as professionals studying for CIPD Level 5 and Level 7 qualifications. Fully aligned with the CIPD Profession Map, this updated 17th edition supports modules in human resource management, employment law and people management. Covering core HR areas including employee relations, learning and development, performance management, reward and talent management, this comprehensive edition also develops essential professional skills such as leadership, conflict management, interviewing and statistical analysis. Updated content explores artificial intelligence in HR, systems thinking, hybrid working, employee wellbeing and the evolving balance of hard and soft HR skills.